Food biotechnology. (December 2020) - Foster, Tim; Adams, Gary; di Bari, Vincenzo; Connerton, Ian; Gould, Joanne; Gouseti, Ourania; Gray, David; Yakubov, Gleb
Abstract : We investigate recent advances in the Chemical Engineering aspects of food structuring agents and macronutrients: carbohydrates, proteins and lipids, and also the fate of food upon ingestion. Prebiotic effects on host-microbe interactions enable improved immune response and pathogen control. Formulation Engineering is an emerging area in the field of Chemical Engineering and requires detailed knowledge of the materials used, and the processes by which they are transformed/functionalised into products. Understanding 'comb-like' polymers and their interactions provide new structuring opportunities. Sustainable sourcing of alternative protein sources, natural lipid organelles and structuring of liquid oils are framed in a waste valorisation approach, utilising biotechnological approaches for new functionalities. Controlling natural and fabricated microstructures enable controlled digestion profiles.